Pengaruh Service Recovery dan Online Customer Review Terhadap Kepuasan Pengguna Lazada - Sherly Rahwati; Arif Fadila (Peneliti.net, 2022)
The purpose of this study is to find out, analyze, and explain the description of each variabel, the magnitude of the relationship between Service Recovery and Online Customer Review, and the amount of influence partially and simultaneosly Service Recovery and Online Customer Review on Lazada Customer Satisfaction. By using quantitave methods and using descriptive analysis (path analysis). Samples taken were 135 respondents. Data collection techniques used are literature and field data collection by ditributing questionnaires online. The results showed that Service Recovery and Online Customer Review have a strong relationship. As well as Service Recovery and Online Customer Review have a positive and significant effect on Customer Satisfaction.